Agrisosioekonomi: Jurnal Transdisiplin Pertanian (Budidaya Tanaman, Perkebunan, Kehutanan, Peternakan, Perikanan), Sosial dan Ekonomi 521 ANALISIS FINANSIAL USAHA KENTANG GORENG â€œPOTATO MODOINDINGâ€ DI KOTA MANADO - Orlan Frenly Maleke; Eyverson ., Ruauw; Ribka Magdalena Kumaat (AGRI-SOSIOEKONOMI, 2019)
This study aims to analyze the financial feasibility of the "Potato Modoinding" french fries business in the city of Manado. This research was carried out in April 2018. The data used are primary data obtained from interviews with owners and business actors (two people) in the form of data: the amount of production, selling price, and investment costs. Data analysis was performed using Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B / C Ratio), Payback Period (PP) and Sensitivity Analysis. The results showed this business was feasible to operate with a value of NPV = 14,045,877, IRR = 0.7623%, Net B / C Ratio = 2.309065, PP = 5 months. The business feasibility limit is when the price of potato raw materials rises by 55%.*eprm*